Wind Farm Facilities in Germany Kill Noctule Bats from Near and Far ... - Lehnert, Linn S.; Kramer-Schadt, Stephanie; Schönborn, Sophia; Lindecke, Oliver; Niermann, Ivo; Voigt, Christian C.; Ratcliffe, John Morgan (Zenodo, 2014)
(Uploaded by Plazi for the Bat Literature Project) Over recent years, it became widely accepted that alternative, renewable energy may come at some risk for wildlife, for example, when wind turbines cause large numbers of bat fatalities. To better assess likely populations effects of wind turbine related wildlife fatalities, we studied the geographical origin of the most common bat species found dead below German wind turbines, the noctule bat (Nyctalus noctula). We measured stable isotope ratios of non-exchangeable hydrogen in fur keratin to separate migrants from local individuals, used a linear mixed-effects model to identify temporal, spatial and biological factors explaining the variance in measured stable isotope ratios and determined the geographical breeding provenance of killed migrants using isoscape origin models. We found that 72% of noctule bat casualties (n = 136) were of local origin, while 28% were long-distance migrants. These findings highlight that bat fatalities at German wind turbines ...